Malay ornament design in modern Malaysian painting volume 1 / Haslinda Abd Razak - Abd Razak, Haslinda (2017)
Malaysian Art has been overshadowed with western influence that leads to identity lost. Subsequently, through the National Cultural Congress in 1971, Malaysian art has promoted diverse types of artwork that captures the distinctiveness of Malaysian identity and one of it through Malay ornament design (MOD). However, a study related to ornament design practices, which addresses in fine art scale has not been conducted comprehensively. This study will emphasize on the usage of Malay ornament design in the Malaysian Modern Painting by Malaysian artist. The aim of the study is to identify types of Malay ornament design adapted by Malaysian painters, to gather appropriate samples as to classify the characteristic aspects that adapted through their creative visual art in painting and to analyse the samples of painting by using the visual analysis and trace the elements of ornament design as requested towards the national identity of Malaysia. The samplings are selected from two publications by National Visual Art Gallery (NVAG) permanent collections particularly focusing from year 1980's until 2008. Twenty-nine paintings have been examined with Ragan (2000) analysis procedures and Sporre (2015) stylistic analysis approaches to investigate these paintings comprehensively. Visual formalistic aspects emphasizing on balance, repetition, space, line, shape and texture are observed in all of the samplings. These images are traced and drawn using Adobe Illustrator CS3© and Adobe Photoshop CS3© software's. This study has identified two major categories of painting with the application of MOD, firstly with thirteenth artwork applied motif and pattern, eight of the samples have been recognized to use MOD with social activities scenery and another five paintings has utilized images or subjects that related to the Malay culture. The second categories consist of three paintings from Islamic design that has utilized geometrical motif and pattern. Mixed media, collage and silkscreen printing techniques are widely used in the composition to capture the uniqueness of ornament design element. This study has signified the application of Malay ornament design in Malaysian Contemporary Art and provides a guideline for fine art practitioners to solve problems in the process of producing artwork using ornament design.